A Novel Approach to Generate Random Numbers Using Fuzzy State Automaton - Dr. Chatrapathy K., Dr. Naveen Kumar B. (International Journal of Control and Automation, 2020)
A novel Pseudo Random Number Generator is developed using a Fuzzy State Automaton. The NIST STS Test Battery 800-221a has been implemented using MATLAB R.2011a. The random bit sequence generated has been tested for expected qualities of randomness, uniformity and independence using visual tests and statistical tests using NIST Test battery. Quality of the random bit sequence generated has been compared with that of true random bits HOT BITS and a standard JAVA random number generator. It is found that the random sequence developed in this work is much simple and powerful and therefore it has very good scope in future cryptographic applications.